International Reserve Management Under Rollover Crises - Barbosa-Alves, Mauricio; Bianchi, Javier; Sosa-Padilla, César (Quarterly Journal of Economics, 2026)
Abstract This article investigates how a government should manage international reserves when it faces the risk of a rollover crisis. We ask: Should the government accumulate reserves or reduce debt to make itself less vulnerable? We show that the optimal policy entails initially reducing debt, followed by a subsequent increase in both debt and reserves as the government approaches a safe zone. Furthermore, we find that issuing additional debt to accumulate reserves can lead to a reduction in sovereign spreads. Evidence from a panel of emerging economies is consistent with these predictions: increases in reserves financed by public external borrowing are associated with lower spreads, and reserve holdings are not systematically drawn down during crisis episodes.